2016
DOI: 10.1002/2016gl070799
|View full text |Cite
|
Sign up to set email alerts
|

Radar imaging of intense nonlinear Ekman divergence

Abstract: In general, given an oceanic thermal front, there is a strong positive correlation between sea surface temperature (SST) gradients and surface winds, and the marine atmospheric boundary layer is unstable over the warm side of the oceanic thermal front. The Gulf Stream is a notable example of an oceanic thermal front, and its warm side is often detected as enhanced backscatter in synthetic aperture radar (SAR) images. However, in some “anomalous” SAR images, low backscatter is sometimes observed on the warm sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Lots of studies have identified that oceanic fronts have a remarkable impact on the regional climate and weather system (G. Q. Liu et al, 2016;Small et al, 2008;Tokinaga et al, 2006;Vecchi et al, 2004;Wallace et al, 1990). For the basin scale, there is a significant negative correlation between SST and surface wind (Namias & Cayan, 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lots of studies have identified that oceanic fronts have a remarkable impact on the regional climate and weather system (G. Q. Liu et al, 2016;Small et al, 2008;Tokinaga et al, 2006;Vecchi et al, 2004;Wallace et al, 1990). For the basin scale, there is a significant negative correlation between SST and surface wind (Namias & Cayan, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Oceanic fronts associated with sea surface temperature (SST) anomalies are considered to be key regions for the midlatitude ocean affecting the overlying atmosphere. Lots of studies have identified that oceanic fronts have a remarkable impact on the regional climate and weather system (G. Q. Liu et al, 2016; Small et al, 2008; Tokinaga et al, 2006; Vecchi et al, 2004; Wallace et al, 1990). For the basin scale, there is a significant negative correlation between SST and surface wind (Namias & Cayan, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The SST fronts over the global oceans, with the large horizontal gradients of the sea surface temperature (SST), are typically accompanied with oceanic jet current. There are extensive studies suggested that SST fronts have a remarkable impact on the regional climate and weather system, including the investigations of SST front on the basin scale (Namias & Cayan, ; Wallace et al, ; Xie, ), as well as the studies with small‐scale of a few kilometers (Liu et al, ; Oneill et al, , ; Small et al, ; Tokinaga et al, ; Vecchi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the enhancement of the wind stress over positive SST anomalies is even greater than one would assume based on the wind speed dependence alone. This effect has implications, for example, for calculating vertical OBL velocities associated with Ekman pumping (Gaube et al 2015), the computation of air-sea exchange processes (Fairall et al 2003), the modeling of surface waves (Cavaleri et al 2007), and the interpretation of remote sensing products from synthetic aperture radar (SAR) and scatterometers (Liu et al 2016).…”
Section: Introductionmentioning
confidence: 99%